Superovulation and embryo recovery in Ongole cows using FSH or equine chorionic gonadotrophin - KASIRAJ, R; RAO, M MUTHA; RANGA REDDY, N S; MISRA, A K; PANT, H C (The Indian Journal of Animal Sciences, 2013)
Cows (32) of Ongole breed were subjected to superovulation trcalment using follicle stimulating hormone (FSH) or equine chorionic gonodotrophin (eCG) and 156 embryos were collected nonsurgically of which 50 were viable. The overall mean ovulation rate, total and viable embryo reconvery rates were 9.09+-0.40, 5.57+-.-0.36 and 1.79+-0.28 respectively. The mean ovulation rate following FSH treatment (10.0+-0.48) was greater (P>0.005) than that with eCG treatment (7.36+-0.71). The mean number of unovulated follicles of >10 mm diameter were similar in both groups. There was significant (P>0.005) difference between groups in the recovery of mean number of total embryos(6.30+-0.43 vs 3.75+-0.66), while the mean viable embryo recovery was similar, Following nonsurgical on transfer of embryos into 15 synchronized recipients, 3 cows conceived.